Reforming Civil Court in Indonesia: The Dialectics Of Procedural Justice and Digital Justice - Umar Mubdi (Mimbar Hukum, 2026)
Abstract This study analyzes new patterns that have emerged in civil justice reform in Indonesia. The functional approach, the common adoptedpattern, has shifted to an institutional approach. This shift, in addition to having an impact on the aspect of judicial governance, also creates dialectics in the form of conceptual tension in understanding justice in the judicial process. This article aims to examine the tension between procedural justice and digital justice. Procedural justice emphasizes the fairness of the process, the participation of the parties, and the legitimacy of the decision. Meanwhile, digital justice is oriented towards efficiency, transparency, and accessibility through technology. This study uses a juridical-normative research method with secondary data sources in the form of laws, regulations, and legal literature. This study also analyzes the development of e-Court, e-Mediation, and the case tracing information system (SIPP) in Indonesia. This research shows that strengthening the rationality of digital systems has the potential to clash with the character of procedural justice centered on human experience. This article also contributes to the formulation of the digital procedural justice framework as a theoretical synthesis of the tension between the two concepts. The framework is positioned as an evaluative tool for assessing technology-based judicial reform that is aligned with the principles of justice, legitimacy, and participation. Abstrak Penelitian ini menganalisis pola baru yang terbentuk dalam reformasi peradilan perdata di Indonesia. Pendekatan fungsional, dalam pola lama, mengalami pergeseran menjadi pendekatan institusional. Pergeseran ini, selain berdampak pada aspek tata kelola peradilan, juga membawa dialektika dalam bentuk ketegangan konseptual dalam memahami keadilan dalam proses peradilan. Artikel bermaksud mengkaji tegangan antara procedural justice dan digital justice. Procedural justice menekankan keadilan proses, partisipasi para pihak, dan legitimasi putusan. Sementara digital justice berorientasi pada efisiensi, transparansi, dan aksesibilitas melalui teknologi. Penelitian ini menggunakan metode penelitian yuridis‑normatif dengan sumber data sekunder berupa peraturan perundang‑undangan dan literatur hukum. Penelitian ini juga menganalisis perkembangan e‑Court, e‑Mediation, serta sistem informasi penelusuran perkara (SIPP) di Indonesia. Penelitian ini menunjukkan bahwa penguatan rasionalitas sistem digital berpotensi berbenturan dengan karakter keadilan prosedural yang berpusat pada pengalaman manusia. Artikel ini juga berkontribusi pada perumusan kerangka digital procedural justice sebagai sintesis teoretis atas ketegangan antara dua konsep tersebut. Kerangka itu diposisikan sebagai alat evaluatif untuk menilai reformasi peradilan berbasis teknologi yang selaras dengan prinsip keadilan, legitimasi, dan partisipasi.